2014
DOI: 10.1086/677255
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity in Federal Criminal Sentences

Abstract: Using rich data linking federal cases from arrest through to sentencing, we find that initial case and defendant characteristics, including arrest offense and criminal history, can explain most of the large raw racial disparity in federal sentences, but significant gaps remain. Across the distribution, blacks receive sentences that are almost 10 percent longer than those of comparable whites arrested for the same crimes. Most of this disparity can be explained by prosecutors' initial charging decisions, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
195
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(209 citation statements)
references
References 29 publications
11
195
0
3
Order By: Relevance
“…In addition, mandatory minimums can have pronounced effects on sentencing outcomes (Kautt and DeLone, 2006;Rehavi and Starr, 2014). Thus, we included mandatory minimum as a binary indicator identifying the 34 offense codes which carried a non-suspendable mandatory prison term.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, mandatory minimums can have pronounced effects on sentencing outcomes (Kautt and DeLone, 2006;Rehavi and Starr, 2014). Thus, we included mandatory minimum as a binary indicator identifying the 34 offense codes which carried a non-suspendable mandatory prison term.…”
Section: Methodsmentioning
confidence: 99%
“…However, the results from these studies have been extremely mixed (see, e.g., Spohn and Cederblom, 1991, finding support for the hypothesis for the disposition decision but not for the duration decision; Spohn and DeLone, 2000, reporting results consistent with the liberation hypothesis for some city-and minority-group combinations but not others; Warren, Chiricos, and Bales, 2012, finding support for the hypothesis among some offender/case type/outcome combinations but not others). Perhaps explanations for these null and even contrary results can be found in the newest wave of contextual disparity research (see, e.g., Kutateladez et al, 2014;Rehavi and Starr, 2014;Starr, 2015). First, not only might stage of the process affect the presence or absence of disparities, but factors like geographic context likely matter (see, e.g., Eisenstein et al, 1988;Kramer and Ulmer, 2009;Ulmer, 1997), and 3 Several researchers have also suggested integrating focal concerns with the liberation hypothesis.…”
Section: Interaction Effects and The Liberation Hypothesismentioning
confidence: 99%
“…While much progress has been made toward these objectives, scholars such as Baumer (2013) and Ulmer (2012) continue to highlight the need for studies that examine not just whether race matters in sentencing, but also how and when race factors into judicial decisionmaking (see also Spohn, 2000). These calls are reinforced by a growing literature that finds racial disparities in certain parts of the criminal justice process but not others (e.g., Blumstein, 1982, Kutateladze et al, 2014Rehavi and Starr, 2014). Moreover, there has been a particular emphasis on the need to examine sentencing practices in a broader variety of contexts-in places other than guidelines jurisdictions like Minnesota, Pennsylvania, Washington, and the federal system, which have dominated the literature (Engen, 2009;Reitz, 2009;Ulmer, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have suggested racial disparities in federal sentences against African-Americans ( Rehavi and Starr, 2014) and the selection of jury members (see Bourke et al, 2003, for Alabama;Initiative, 2010, for Louisiana). Thus, historical scars of racism may still linger in the US justice system.…”
Section: Introductionmentioning
confidence: 99%